An experimental investigation on heat transfer characteristics arising over an underfloor cooling system exposed to different radiant heating loads through walls - Karakoyun, Yakup; Acikgoz, Ozgen; Yumurtaci, Zehra; Dalkilic, Ahmet Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
In the present study, four different surface configurations have been created, one corresponding to only cooling by the floor, whereas, three of them pertaining to simulations in each, one more sidewall has been used as a heat gain of the experimental chamber. The underlying reason behind sidewalls to be used as heat gain sources is that especially under hot climate conditions, uninsulated or improperly insulated walls of buildings to cause undesired heat gains. To experimentally realize these thermal conditions, tests have been performed within supply water mass flow rate and temperature ranges of 0.056 kg/s - 0.200 kg/s and 10 degrees C to 20 degrees C, respectively. Sidewalls' temperatures have been selected between 22 degrees C and 40 degrees C, to utilize them as heat gain sources. Relatively higher values of convective heat transfer coefficients are obtained compared to relevant literature within the range of 5-20%, while similar tendencies are seen in radiation results. Correlations are recommended for total, radiative, and convective heat fluxes whose deviations from the data are 5%, 5%, and 15%, respectively. Furthermore, a physical mechanism based comparison with regard to heat transfer coefficients is made between the radiant floor cooling results and the ones corresponding to radiant floor heating system.
Keywords: Radiant floor cooling; Power economy; Hydronic system; Radiant design standards; TRANSFER COEFFICIENTS; FLOOR; PERFORMANCE; BUILDINGS; Thermodynamics; Energy & Fuels; Engineering; Mechanics